2022
DOI: 10.1042/cs20211122
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A1 treatment prevents the evolution to fibrosis of experimental nonalcoholic steatohepatitis

Abstract: Annexin A1 (AnxA1) is an important effector in the resolution of inflammation which is involved in modulating hepatic inflammation in nonalcoholic steatohepatitis (NASH). In this study we have investigated the possible effects of treatment with AnxA1 for counteracting the progression of experimental NASH. NASH was induced in C57BL/6 mice by feeding methionine-choline deficient (MCD) or Western diets and the animals were treated for 4-6 weeks with human recombinant AnxA1 (hrAnxA1; 1µg, daily IP) or saline once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Thus in a recent study, Gadipudi, Ramavath, Provera et al investigated how treating mice with NASH with recombinant human AnxA1 (hrAnxA1) would influence disease. Interestingly, they found that while this treatment had no effect on metabolic syndrome or hepatic steatosis, it did reduce liver inflammation and fibrosis in two different mouse models of NASH, suggesting this may be a relevant target for therapeutic intervention [ 9 ].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Thus in a recent study, Gadipudi, Ramavath, Provera et al investigated how treating mice with NASH with recombinant human AnxA1 (hrAnxA1) would influence disease. Interestingly, they found that while this treatment had no effect on metabolic syndrome or hepatic steatosis, it did reduce liver inflammation and fibrosis in two different mouse models of NASH, suggesting this may be a relevant target for therapeutic intervention [ 9 ].…”
mentioning
confidence: 99%
“…In the present study, NASH was first induced by feeding mice either a methionine and choline deficient diet for 4 weeks or a Western diet for 10 weeks and then continuing mice on the diets for an additional 4 or 6 weeks, respectively, in which the mice were treated 5 times per week with hrAnxA1 (intraperitoneal administration). This led to a reduction in the serum alanine aminotransferase levels (sALT) and ameliorated the global histological scoring for lobular inflammation [ 9 ]. Furthermore, collagen staining with Sirius Red shows a reduction of collagen deposition in mice treated with hrAnxA1, although no changes were detected in terms of steatosis and liver triglyceride content.…”
mentioning
confidence: 99%
See 3 more Smart Citations